Platyfish bypass the constraint of the caudal fin ventral identity in teleosts. Issue 11 (22nd July 2022) - Rees, Lana; König, Désirée; Jaźwińska, Anna
Abstract: Background: The caudal fin of teleosts is characterized by dorsoventral symmetry. Despite this external morphology, the principal rays of this appendage connect to bones below the notochord, indicating the ventral (hypochordal) identity of this organ. Results: Here, we report that this typical architecture of the caudal fin is not fully conserved in the platyfish ( Xiphophorus maculatus ) and the guppy ( Poecilia reticulata ), representatives of the Poeciliidae family. We show that in these species, 3–4 principal rays connect to bones above the notochord, suggesting an epichordal contribution. Consistently, as examined in platyfish, dorsal identity genes zic1 / 4 were highly expressed in these rays, providing molecular evidence of their epichordal origin. Developmental analysis revealed that the earliest rays above the notochord emerge at the 10‐ray stage of fin morphogenesis. In contrast to zebrafish and medaka, platyfish and guppies display a mirrored shape of dorsal and ventral processes of the caudal endoskeleton. Our study suggests that an ancestral bauplan expanded in poeciliids by advancing its symmetrical pattern. Conclusion: The platyfish evolved a fin architecture with the epichordal origin of its upper principal rays and a high level of symmetry in the caudal endoskeleton. This innovative architecture highlights the adaptation of the teleost skeleton. Key Findings: In platyfish, principal rays of the caudal fin are associated with endoskeletal elements not only below but also above the notochord. Dorsal identity markers zic1/4 are highly expressed in the three uppermost principal rays. The epichordal principal rays begin to form at the developmental stage with 10 caudal rays. The caudal fin of platyfish displays a striking internal symmetry of the endoskeleton.